2016
DOI: 10.1097/icu.0000000000000238
|View full text |Cite
|
Sign up to set email alerts
|

Glaucoma management after vitreoretinal surgeries

Abstract: Purpose of review The surgical management of retinal disorders, including scleral buckling procedures, pars plana vitrectomy, and intravitreal injections of gas or silicone oil, can lead to short-term elevations in intraocular pressure (IOP) and ultimately long-term glaucomatous damage if not treated in a timely manner. Glaucoma in these cases is commonly refractory to conventional therapies. This review highlights the treatment strategies for glaucoma in eyes that have previously undergone vitreoretinal surge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 89 publications
(80 reference statements)
1
36
0
1
Order By: Relevance
“…Transient and sustained elevation of IOP is a relatively common occurrence following surgery to repair retinal detachment. The reported range of incidence of IOP elevation in the literature ranges from 4.8% to 44%, while modern literature reports a range of 11.6–12.9% 915. The calculated incidence obtained from the study is consistent with rates reported in other studies.…”
Section: Discussionsupporting
confidence: 86%
“…Transient and sustained elevation of IOP is a relatively common occurrence following surgery to repair retinal detachment. The reported range of incidence of IOP elevation in the literature ranges from 4.8% to 44%, while modern literature reports a range of 11.6–12.9% 915. The calculated incidence obtained from the study is consistent with rates reported in other studies.…”
Section: Discussionsupporting
confidence: 86%
“…Although intravitreal injection of SO in vitreoretinal surgeries can cause post-operative secondary glaucoma in humans(30, 31), we reasoned that direct injection of SO into the anterior chamber of mice would be more efficient, preventing the need to remove the vitreous and reducing toxicity due to direct contact with the retina. As illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A well-documented, secondary glaucoma with acutely elevated IOP occurs as a post-operative complication following the intravitreal use of silicone oil (SO) in human vitreoretinal surgery(30, 31). SO is used as a tamponade in retinal detachment repair due to it being buoyant with high surface tension.…”
Section: Introductionmentioning
confidence: 99%
“…Examinations included best-corrected visual acuity (BCVA), IOP, anterior segment detection by slip lamp and fundus examination via indirect ophthalmoscopy. Eyes with IOP ≥ 30 mmHg were treated with topical or systemic antiglaucomatous medication, anterior chamber paracentesis, laser iridoplasty, and inferior iridectomy [9]. Oil removal with or without concurrent glaucoma surgery may be required in eyes with uncontrolled high IOP after silicone oil injection.…”
Section: Follow-up and Treatment For Iop Elevation Postoperativelymentioning
confidence: 99%